Transient Neonatal Diabetes Mellitus in SHORT Syndrome: A Case Report - Kim, Shin-Hee; Kim, Minsung; Yim, Jisook; Kim, Myungshin; Jang, Dae-Hyun (Frontiers in Pediatrics, 2021)
SHORT syndrome is a rare autosomal dominant disorder characterized by multiple congenital defects and is historically defined by its acronym: short stature, hyperextensibility of joints and/or inguinal hernia, ocular depression, Rieger anomaly, and teething delay. Herein, we report a male infant with SHORT syndrome who presented with transient neonatal diabetes mellitus (TNDM) with insulin resistance. The proband was born at 38 weeks of gestation but displayed facial dysmorphic features. Intrauterine growth restriction (IUGR) was detected on a prenatal ultrasonography test. His birth weight was 1.8 kg (< 3rd centile), length 44 cm (< 3rd centile), and head circumference 31 cm (< 3rd centile). The patient’s blood glucose level started to increase at 5 days of age (218‒263 mg/dL) and remained high at 20 days of age (205–260 mg/dL). He was treated with subcutaneous insulin and the blood glucose level gradually stabilized. Blood glucose level was stabilized over time without insulin treatment at 6 weeks of age. Clinical exome sequencing showed a heterozygous pathogenic variant, NM_181523.3:c.1945C>T (p.Arg649Trp) in exon 15 of the phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) known as the causative gene for SHORT syndrome. Examination of the patient at 10 months of age revealed no experience of any hyperglycemic episode and glycated hemoglobin level was 5.2%. To the best of our knowledge, this is the first case of TNDM in SHORT syndrome due to a pathogenic variant of PIK3R1. We believe that our case can aid in expanding the phenotypes of SHORT syndrome.